Genetics of resistance to Striga and Alectra in cowpea - Atokple, I.; Singh, B.; Emechebe, A. (1995)
The parasitic weeds Striga gesnerioides (Willd.) Vatke and Alectra vogelli (Benth.) cause considerable demage to cowpea [ Vigna unguiculata (L.) Walp] in the semiarid regions of Africa. Systematic screening has revealed few cowpea varieties to be resistant. Of these, B 301 is resistant to both striga and alectra; IT82D-849 is resistant to striga but susceptible to alectra; SUVITA-2 Is resistant to striga In Burkina Faso only but susceptible to alectra, and IT81D-994 is moderately resistant to striga as well as alectra. Previous genetic studies revealed a single dominant gene for striga and duplicate dominant genes for alectra resistance in B 301. This study was undertaken to elucidate the mode of inheritance of striga resistance in IT82D-849 and establish allelic relationships among genes for resistance to striga and alectra in other varieties. Relevant genetic populations were screened using pot culture technique. Results showed that resistance in IT82D-849 to striga also is controlled by a single dominant gene but is different from that found in B 301. Also, the single dominant gene possessed by SUVITA-2 against the striga strain from Burkina Faso is nonallelic to the single dominant genes in B 301 and IT82D-849. The duplicate dominant genes in B 301 against alectra are nonallelic to a single gene in IT81D-994. Screening the parents of IT82D-849 and allelic test revealed that its source of striga resistance is from Emma 60. Gene symbols Rsg 1 , Rsg 2 , and Rsg 3 are proposed for resistance to Striga gesnerioides In B 301, IT82D-849, and SUVITA-2, respectively, and gene symbols Rav 1 , Rav 2 , and Rav 2 , are proposed for resistance to Alectra vogelli in B 301 and IT81D-994.